Republic of Estonia : 2018 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the economy of Estonia is gathering steam after several years of subdued growth. Real GDP grew by 4.9 percent in 2017, more than double the rate achieved a year earlier. Growth remains broad-based, and supported by strong private and public investment-the latter partly reflecting increased absorption of European Union structural funds-and favorable external conditions. However, output runs above its sustainable level, and supply-side constraints are becoming more binding. The outlook is positive. Over the medium term, growth is set to remain at about 3.5 percent, supported by the continuing recovery of main trading partners, domestic investment, accommodative financial conditions, and continued strong market sentiment.